Medicinal effects of nigella sativa in gynecological disorders: a systematic review - Deepthika, S.H.K.; Karunagoda, K.P.K.R.; Perera, P.K. (International Journal of Pharmaceutical Sciences and Research, 2022)
Comprehensive search of previously published research was conducted in PubMed, Science Direct, Scopus, and Google Scholar databases for studies published between 2012 and August 2021. The keywords used in combination to search for articles included Nigella sativa and “Gynecology”. In the first stage, the total articles obtained from searching the above databases using the above keywords were pooled together, and duplicate articles were removed. The remaining articles were primarily screened by reading the title and abstracts and selecting the most relevant articles. In the last stage, articles were reviewed again by reading the entire article, and those that did not meet the inclusion requirements were eliminated. A manual search was conducted using the reference list of the included research publications to collect additional data. In the various databases, the literature search found the following number of research articles: PubMed (n=11), Science Direct (n=35), Scopus (n=07), and Google Scholar (n=1070). After removing duplicates, there were 1062 articles. Those articles were further screened first by reading topics and abstracts and secondly, reading full text that did not match the inclusions was removed. After removing those articles, there were 40 articles, and after adding 05 manual search articles, finally, 45 articles were included in the systematic review. Nigella sativa has medicinal benefits for gynecological disorders such as PCOS, menopause-related issues, Hyperprolactinemia, Candidiasis, Trichomoniasis, Cervical cancer, Breast cancer, ovarian cancer, Premenstrual syndrome and Pre-eclampsia. Nigella sativa also improves endometrium, oocyte maturity and quality and reduces ovarian tissue damage without any adverse effects
Keywords: Nigella sativa; Black cumin; Medicinal effects; Gynecological disorders